Value of Touch Preparation Cytology in Intraoperative Consultation Diagnosis of Astrocytomas - Nasir, Humaira; Haque, Anwar Ul (International Journal of Pathology, 2018)
Intra-operative diagnosis of brain tumours routinely employs frozen sections. The frozen section however has severallimitations and induces serious freezing artefacts. We carried out a prospective study on 40 cases of astrocytomas utilizingtouch preparation cytology. The smears were quite cellular with crisp cellular details. There was 98.4% sensitivity and 90%specificity. We found touch preparation cytology highly reliable mode of intra-operative diagnosis in astrocytomas.